What's Love Got to Do with It? Women, the Egyptian Muslim Brotherhood and Organisational Identity - Biagini, Erika (PARTECIPAZIONE E CONFLITTO, 2021)
The article suggests that the gender politics advanced by the young female members of the Egyptian Muslim Brotherhood in the family sphere after the 2013 military-led coup challenges the movement's ability to re-emerge from repression based on traditional patriarchal values and principles. A patriarchal division of labour, epitomized in women's position in the family, sustains the Brotherhood in times of repression and in its absence. The research shows that the circumstances of repression against the movement have caused women to reconsider the Brotherhood's patriarchal structures, with potential consequences for the organisation. The article does so by analysing women's articulations of their role in the family and in marriage relationships. Using love as an analytical lens, the article argues that women's demand for love in marriage suggest their desire to commit the Brotherhood to attending women's needs, desires and aspirations.